OPTIONS FOR CREATING A WAREHOUSE NETWORK IN THE LAST MILE LOGISTICS (Perner's Contacts, 2020)
Modern logistics practice aims at comprehensive problem solving and full integration of supply chains. One of the areas in which an effective solution needs to be found is the creation of a warehouse network. Finding a suitable model for the location of distribution or storage centers, which would, in addition to cost savings or profit maximization, also take into account the time aspect, can lead to gaining a competitive advantage. Applying such a model to the conditions of current trends in the field of last mile logistics could then lead not only to gaining a competitive advantage, but also to gaining a larger market share. The aim of this article is to explore the possibilities of using existing methods and models used to create a distribution network, such as static methods, in which warehouses or service centers can be distributed according to purpose, and according to their nature can use continuous, discrete or network models. Furthermore, the article examines the possibilities of using dynamic models, which are more focused on the time factor and could be used to allocate warehouses or distribution centers, among other things, in last minute logistics, because the current trend is the time aspect of when companies they are currently working to reduce delivery times as much as possible. The article deals with possibilities of using location-allocation problem, P-median model, Weber's model, or the concept of the problem of warehouse location as non-dimensioned problem of equipment location. The fact that these models do not take into account customers and benefits for customers proves to be problematic with the above-mentioned models. It is therefore necessary to focus on finding a model that takes into account certain elements of customer service, such as easy product availability, delivery frequency or delivery time requirements, not only in the case of last mile logistics. From above mentioned methods, based on the time factor, the best for the deployment of distribution centers appears to be a combination of logistics method Quality function deployment (QFD), which allows to incorporate customer requirements into the final product in combination with the method Analytic network process. Unstructured situations on simpler components, possibly with the Analytic hierarchy process method, focused on network decision problems in order to determine the optimal location for the warehouse or distribution center. The aim of this article is to explore the possibilities of using a combination of the above models for the deployment of warehouses or distribution centers in last mile logistics.
Keywords: global logistics; distribution centre; supply chain; modelling; lacation tasks; last mile logistics